Charting the landscape of presence in virtual reality research: a bibliometric review - Williams, Philip; Kelly, Michelle A.; Rowett, Debra; Gwilt, Ian (Frontiers in Virtual Reality, 2025)
IntroductionAs a defining feature of virtual reality, the sense of presence has been a focal point of research for decades. Navigating the extensive body of presence research can be challenging, yet it is essential for understanding the evolution of the concept over time, recognising the contributions of key scholars, and charting new research pathways. This study applied a bibliometric analysis to map networks of influence and conceptual frameworks spanning over 30 years of presence research to highlight the disciplines, authors, articles, and concepts that have gained prominence in scholarly discourse.MethodBibliographic data for 6636 documents from 1992 to 2024 were extracted from Web of Science (WoS) and Scopus citation indexes for analysis using Biblioshiny and VOSviewer. Outputs from WoS and Scopus databases were combined to provide high-quality bibliographic records for co-occurrence, co-citation, and bibliographic network analysis using Biblioshiny and VOSviewer. An extended analysis of contemporary research discusses considerations for presence research.ResultsPublication output since 2015 has grown rapidly. A source analysis reflects a dominance of the discipline of computer science and engineering, while interdisciplinary connections in applied settings are an emerging area of growth. Citation and publication output are heavily dominated by the top 10 authors, indicating a reliance on relatively few contributors. Terminology that co-occurs with presence remains dominated by the technical aspects of immersion and experience design, while also reflecting more recent growth in the use of virtual reality in applied settings. This demonstrates that recent contributors and newer concepts have yet to be significantly reflected in global presence research.DiscussionThis analysis underscores the need to view presence as a multidimensional construct that requires a multidisciplinary approach and methodologies providing user-centred, holistic perspectives that embrace the nuances of individual psychological experiences. The present bibliometric review provides a valuable overview of the evolving landscape of presence research as a complement to previous, more focused systematic and scoping reviews. This bibliometric analysis of the past 30 years of research demonstrates that presence remains a defining concept in virtual reality and a field that warrants further investigation and development to achieve compelling, relevant and memorable virtual reality experiences.